Acute particulate matter exposure diminishes executive cognitive functioning after four hours regardless of inhalation pathway - Thomas Faherty; Jane E. Raymond; Gordon McFiggans; Francis D. Pope (Nature Communications)
Abstract Recent evidence suggests short-term exposure to particulate matter (PM) air pollution can impact brain function after a delay period. It is unknown whether effects are predominantly due to the olfactory or lung-brain pathways. In this study 26 adults (M a g e  = 27.7, S D a g e  = 10.6) participated in four conditions. They were exposed to either high PM concentrations or clean air for one hour, using normal inhalation or restricted nasal inhalation and olfaction with a nose clip. Participants completed four cognitive tests before and four hours after exposure, assessing working memory, selective attention, emotion expression discrimination, and psychomotor vigilance. Results showed significant reductions in selective attention and emotion expression discrimination after enhanced PM versus clean air exposure. Air quality did not significantly impact psychomotor vigilance or working memory performance. Inhalation method did not significantly mediate effects, suggesting that short-term PM pollution affects cognitive function through lung-brain mechanisms, either directly or indirectly.